EVALUASI KERUSAKAN BETON DAN METODE PERBAIKAN - F.Eddy Poerwodihardjo; Dwi Istiningsih (Teodolita: Media Komunkasi Ilmiah di Bidang Teknik, 2020)
Massive use of concrete in building construction requires an evaluation of the quality and implementation of work so that construction can function according to the age of the plan. It aims to determine the ability of  a  structure  that  is  analyzed  systematically,  including  the  dimensions  of  geometry,  materials,  and current structural conditions. Concrete construction that is strong and durable requires the selection of quality materials and the process of implementing a perfect concrete.  If  damage  occurs,  it  is  necessary  to  carry  out  continuous  evaluations  and  repair  concrete  as  well  as structural  reinforcement.  So  that  the  concrete  construction  function  returns  to  good  performance. Damages that often occur include: porous, disintegration and weathering of materials, corrosion of steel reinforcement, cracks on concrete plates, honeycomb / hollow concrete and uneven concrete or bulging on the surface. Methods of improvement that can be done include: chipping and concreting, strengthening, shot concrete, grouting,  jacketing  and  patching  or  sealing.  The  method  of  repairs  carried  out  must  be  in  accordance with the evaluation of damage and cost factors. Keywords: concrete, damage, repair ABSTRAKPenggunaan  beton  pada  konstruksi  bangunan  secara  masif  memerlukan  evaluasi  mutu  dan  pelaksanaan pekerjaan  agar  konstruksi  dapat  berfungsi  sesuai  umur  rencana.  Hal  ini  bertujuan  untuk  mengetahui kemampuan  dari  sebuah  struktur  yang  dianalisa  secara  sistematik,  meliputi  dimensi  geometri,  bahan material, dan kondisi struktur terkini. Konstruksi beton yang kuat dan awet memerlukan pemilihan bahan yang bermutu dan proses pelaksanaan beton yang sempurna. Bila  terjadi  kerusakan,  perlu  diadakan  evaluasi  secara  terus  menerus  dan  dilakukan  perbaikan  beton maupun  perkuatan  struktur.  Sehingga  fungsi  konstruksi  beton  kembali  pada  performa  yang  baik. Kerusakan  yang  sering  terjadi  antara  lain  :  keropos,  disintegrasi  dan  pelapukan  bahan,  korosi  tulangan baja, retak pada plat dak beton, honeycomb/beton berongga dan beton yang tidak rata atau menggembung pada permukaannya. Metode  perbaikan  yang  dapat  dilakukan  antara  lain  adalah  :  chipping  and  concreting,       strengthening, shot  crete,  grouting,  jacketing  dan  patching  or  sealing.  Metode  perbaikan  yang  dilakukan  harus  sesuai dengan evaluasi kerusakan yang terjadi dan faktor biaya. Kata kunci : beton, kerusakan, perbaikan